2018
DOI: 10.23910/ijbsm/2018.9.2.1862
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Tomato (Solanum lycopersicum L.) Hybrids for Yield and its Contributing Traits under Mid-hill Conditions of Himachal Pradesh

Abstract: With an objective to estimate the performance of tomato hybrids with respect to their yield and yield contributing traits, an experiment was conducted at the experimental farm of RHR&TS, Jachh, Kangra, Himachal Pradesh with 20 hybrids along with their 12 diverse parents and standard check Naveen 2000+, which is a leading commercial tomato hybrid in Himachal Pradesh. The hybrids were produced during Rabi 2015 by following line×tester mating design and were evaluated during kharif, 2016. The later experiment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…L7 (6.30%), L17 (5.10%), and L2 (4.75%) had the highest brix values, whereas L5 (2.60%) and L20 (2.85%) had the lowest brix values. Brix values of different tomato genotypes ranged from 3.12% to 6.03% Giorio et al, 2007;Pal et al, 2018;Raj et al, 2018). However, Hanson et al (2004) found that brix values ranged from 3.6 to 8.6% among L. esculentum, L. pipinellifolium genotypes.…”
Section: Resultsmentioning
confidence: 96%
“…L7 (6.30%), L17 (5.10%), and L2 (4.75%) had the highest brix values, whereas L5 (2.60%) and L20 (2.85%) had the lowest brix values. Brix values of different tomato genotypes ranged from 3.12% to 6.03% Giorio et al, 2007;Pal et al, 2018;Raj et al, 2018). However, Hanson et al (2004) found that brix values ranged from 3.6 to 8.6% among L. esculentum, L. pipinellifolium genotypes.…”
Section: Resultsmentioning
confidence: 96%